The Role of Media Exposure in Moderating the Effect of Green Investment, Environmental Performance, and Financial Slack on Carbon Emission Disclosure - Tri Utami; Dila Angraini; Dea Annisa (KEUNIS, 2026)
Purpose: The purpose of this study is to investigate and gather empirical data about how media exposure influences the disclosure of carbon emissions in relation to green investment, environmental performance, and financial slack. Companies in the energy and basic minerals sectors that are listed on the Indonesia Stock Exchange were the subject of this study. This study utilized purposive sampling, and there were a total of 17 companies included in the sample. Methodology: Multiple linear regression and moderated regression analyses were employed in this study, while Eviews version 12 was utilized for data processing. Results: According to this study, environmental performance and financial slack have a favorable impact on carbon emission disclosure, whereas green investment shows a marginal effect. Besides, the impact of financial slack, environmental performance, and green investment on carbon emission disclosure was not mitigated by media exposure. Novelty: The moderating variable for carbon emission disclosure in this study was media exposure. Since the media has a significant influence on public perception and legitimacy demands on businesses, media exposure was selected as a moderating variable. The association between internal corporate parameters and carbon emissions is strengthened when firms with strong environmental performance, green investment, and financial capability are encouraged by high media exposure to disclose carbon emissions more transparently.